I'm new to Python, I found the below recursive program being tough to follow. While debugging the program I could find that it goes through recursion and the value of k
decrements -1 every time we recurse. At one point k
is -1 and the compiler moves to the else
part and returns 0.
Finally, the k
value turns out to be 1, how does this happen?
def tri_recursion(k):
if(k>0):
result = k+tri_recursion(k-1)
print(result)
else:
result = 0
return result
print("\n\nRecursion Example Results")
tri_recursion(6)
And the output:
Recursion Example Results
1
3
6
10
15
21
Try tracing the function with a pencil and paper. In this case, the print statement insde the function may be a bit misleading.
Consider this part of the program,
if(k>0):
result = k+tri_recursion(k-1)
...
From here,
tri_recursion(6) = 6 + tri_recursion(5)
So to get the result for tri_recursion(6)
we must get the result of tri_recursion(5)
Following this logic, the problem reduces to:
tri_recursion(6)
= 6 + tri_recursion(5)
= 6 + 5 + tri_recursion(4)
= 6 + 5 + 4 + tri_recursion(3)
= 6 + 5 + 4 + 3 + tri_recursion(2)
= 6 + 5 + 4 + 3 + 2 + tri_recursion(1)
= 6 + 5 + 4 + 3 + 2 + 1 + tri_recursion(0)
Now notice that 0 is not greater than 0 so the program moves to the body of the else clause:
else:
result = 0
...
Which means tri_recursion(0) = 0
. Therefore:
tri_recursion(6)
= 6 + 5 + 4 + 3 + 2 + 1 + tri_recursion(0)
= 6 + 5 + 4 + 3 + 2 + 1 + 0
= 21
k
is never equal to -1
, infact it is impossible.if you debug the code like this
def tri_recursion(k):
if(k > 0):
print('\t'*k,'start loop k',k)
holder = tri_recursion(k - 1)
result = k + holder
print('\t'*k,'i am k(', k,')+previous result(', holder,')=',result)
else:
result = 0
print('i reached when k =', k)
print('\t'*k,'end loop', k)
return result
print("\n\nRecursion Example Results")
tri_recursion(6)
you will see the output like
Recursion Example Results
start loop k 6
start loop k 5
start loop k 4
start loop k 3
start loop k 2
start loop k 1
i reached when k = 0
end loop 0
i am k( 1 )+previous result( 0 )= 1
end loop 1
i am k( 2 )+previous result( 1 )= 3
end loop 2
i am k( 3 )+previous result( 3 )= 6
end loop 3
i am k( 4 )+previous result( 6 )= 10
end loop 4
i am k( 5 )+previous result( 10 )= 15
end loop 5
i am k( 6 )+previous result( 15 )= 21
end loop 6
21
If you love us? You can donate to us via Paypal or buy me a coffee so we can maintain and grow! Thank you!
Donate Us With